Clock-controlled rhythmic transcription: is the clock enough and how does it work? - Beytebiere, Joshua R (Transcription, 2019)
Circadian clocks regulate the rhythmic expression of thousands of genes underlying the daily oscillations of biological functions. Here, we discuss recent findings showing that circadian clock rhythmic transcriptional outputs rely on additional mechanisms than just clock gene DNA binding, which may ultimately contribute to the plasticity of circadian transcriptional programs.